Health Risk Assessment of Pesticides in Drinking Water in South Africa - A case study on Piketberg and Withoogte drinking water treatment plants along Berg River applying QCRA - Pettersson, Malin; Engman, Mia (My University, 2022)
Pesticides are applied to a broad extent within the South African agricultural sector. The sector lack clear regulations regarding the amount applied or which pesticides are legally permitted to use. Exposure to pesticides has been recognized as one of the main chemical threats to human health globally. Watercourses are often surrounded by agricultural land and the spread of pesticides from these lands poses a risk to the aquatic environment. Berg River is a watercourse located in an agricultural area in the Western Cape, South Africa. The river is used as raw water source for the two drinking water treatment plants, DWTPs, Piketberg and Withoogte. Hence, pesticides may pose a risk to the quality of the drinking water. Consequently, this thesis aims to investigate if long-term exposure to pesticides in drinking water poses a human health risk. A quantitative chemical risk assessment, QCRA, was conducted to evaluate the health risk. The pesticides atrazine, imidacloprid and simazine were analysed for different population groups; infants, children and adults, and three different scenarios in the DWTPs. These scenarios included normal operation, lack of treatment and normal operation with the addition of a granular activated carbon filter, GACfilter. Field studies were conducted at both DWTPs where raw water and drinking water samples were collected. The remaining input for the QCRA-model was compiled through a literature study. A sensitivity analysis was performed to evaluate which input affected the result the most. There were detectable levels of all studied pesticides in the raw water and the drinking water. However, the study concluded that there is no human health risk for long-term consumption of drinking water from Piketberg DWTP and Withoogte DWTP for any of the scenarios. Infants that are formula-fed was the population group that was prone to the highest health risk when exposed to simazine. Adding a GAC-filter resulted in lower concentrations of pesticides in drinking water.
Keywords: QCRA; Pesticides; Atrazine; Imidacloprid; Simazine; Berg River; Piketberg; Withoogte; South Africa; Sensitivity analysis; Health risks; Water treatment